Isoscattering point in SANS contrast variation study of aqueous magnetic fluids. (2nd November 2022) - Tomchuk, Oleksandr V.; Bulavin, Leonid A.; Avdeev, Mikhail V.
ABSTRACT: Small-angle neutron scattering (SANS) is widely used in structural analysis of complex liquid dispersions. An essential feature of SANS experiments for such systems is hydrogen/deuterium isotopic substitution in liquid media, which makes it possible to change the neutron scattering length density of the solvents, thus providing the basis for the contrast variation technique. In some cases, for dispersed particles with near-spherical symmetry, one can observe in the scattering curves specific points at which the scattered intensity is independent of the scattering contrast between dispersed particles and solvent. These points are referred to as 'isoscattering points' and in monodisperse solutions related to the particle size. Here, we report this effect for rather polydisperse (above 40%) magnetic fluids with core-shell particles in a liquid medium (water). It is shown that the effective isoscattering point can be analyzed to some extent for polydisperse systems, which gives additional possibilities for structural characterization of complex solutions via SANS.